English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-12 19:42:33 · 3 answers · asked by Emily S 1 in Science & Mathematics Mathematics

3 answers

9 log[base b](x) - 3 log[base b](y)

First, move the 9 and the 3 inside the log as a power.

log[base b](x^9) - log[base b](y^3)

Now, combine the logs; note that a difference of logs means division inside the log.

log[base b]( x^9 / y^3 )

2007-03-12 19:49:46 · answer #1 · answered by Puggy 7 · 0 0

9log(b)x-3log(b)y=log(b)(x^9)-log(b)(y^3)
=log(b)((x^9)/(y^3))
=log(b)((x^3/y)^3)
=3log(b)(x^3/y)

2007-03-13 03:45:07 · answer #2 · answered by beuuu 2 · 0 0

=log(b)x^9-log(b)Y^3
=log(b)[x^9/y^3]
=log(b)[{x^3/y}^3]
=3log(b)[x^3/y]

2007-03-13 02:53:50 · answer #3 · answered by yogesh gulhania 2 · 0 0

fedest.com, questions and answers